Edible Fruits and Berries as a Source of Functional Polyphenols: Current Scene and Future Perspectives - Echeverria-Morgado, J (Springer Science and Business Media B.V., 2025)
In recent years, there is a growing interest in nutraceutical-rich functional foods for promoting human health. Wild fruits and berries are excellent sources of phytochemicals even though the most deeply studied are the polyphenolic compounds, among them, the major ones such as flavonoids, anthocyanins, or tannins. This review aimed to comprehensively analyze the currently available literature on wild edible fruits and berries, since these fruits are characterized for their high content of polyphenolic compounds. Moreover, both intrinsic (ripening and genetic variability) and extrinsic (environmental conditions: habitat, light, temperature) factors where considered since they affect the polyphenolic content in these fruits. Besides, the therapeutic potential of berries for treating human diseases was assessed through the revision of in vivo and in vitro assays and clinical studies, having in mind that most of these effects are exerted due to their antioxidant capacity. Furthermore, recent challenges and future trends on the research and utilization of wild fruits and berries were addressed to complete the overview of this sustainable source of natural ingredients. Finally, ScienceDirect, Scopus, and Google Scholar were the databases used for the compilation of the information present in this review, selecting the more recent studies and comparing from a critical point of view, the information found. Thus, this review compiled information of berries regarding their polyphenolic content and the variations this suffer depending on different variables; the potential use of the berries for a therapeutic application; and the trends and challenges that the use of berries faces after the research done. © The Author(s), under exclusive licence to Springer Nature B.V. 2023.